Edukasi Konsep Safe Touch dan Unsafe Touch bagi Anak Melalui Alat Peraga Wayang Kertas di Komunitas - Vinny Alvionita; Aditya Febriliansyah; Nur Aisyah Wahyuni; Adela Febriana; Retna Tria Pristica; Linda Ayu Setya Indra Susanti; Huzaimah Huzaimah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Sexual violence against children is a crucial issue that requires the active role of various parties, including educators and the community, in prevention efforts. This community service aims to increase children's understanding at the BERKAH AR-RAHIM Tarakan Orphanage about the concept of safe touch and unsafe touch through education based on educational props (APE) in the form of paper puppets. The activity will be held on December 25 2024 carried out in three educational sessions which include educational demonstrations, guided discussions, and simulative exercises using paper puppets which are designed to be interesting and age appropriate. A total of 24 children were involved in this activity, and the evaluation results showed a significant increase in children's understanding of self-protection against sexual violence. Before the activity, most children had a low level of understanding, but after the activity took place, there was an increase to 75% of children reaching the good understanding category. This activity shows that a visual-based educational approach is able to simplify complex concepts and make it easier for children to understand self-protection messages. Using paper puppets as an educational medium has proven to be an effective and fun method. It is hoped that this activity can become a preventive education model that can be applied to prevent sexual violence against children